Ijbar Nikah di Kampung Sidosermo Dalam Surabaya Perspektif Hukum Islam - Abdulloh Faqih Putro Argo; Mokhammad Rizky Khoirul Amin; Muh Nurkholis; Abdul Rouf; Nur Lailatul Musyafa’ah (AL-HUKAMA, 2020)
This article discusses about the forced marriage in Sidosermo Dalam Surabaya to be analyzed by Islamic law. This research is field research and is qualitative in nature. Data were collected through interviews and documentation, then analyzed deductively. The forced marriage still occurs in Sidosermo Dalam Surabaya. Marriage was motivated by several reasons: the factor of parents' concern for their child, the factor of family relations, the existence of myths, the existence of Syafii's understanding of fiqh that allows the forced marriage, and economic factors. The forced marriage can occur in girls and boys even though they are adults. In Islamic law, all schools of thought think that the permissible marriage permit is for girls who are not yet mature, while for those who are adults or who are widows there is a dispute between the imam of the mazhab. In the KHI, the forced marriage should not occur because the marriage can be carried out with the consent of the two prospective brides.